Challenges of Canteen Intervention for Diabetes Prevention in the Worksite Set Up of Eastern Nepal - Pyakurel, Prajjwal; Parajuli, Hom Bahadur; Gurung, Ranjana (Journal of College of Medical Sciences-Nepal, 2018)
NA